A framework for QoS-Aware service-based mobile systems - Gonçalves, Joel (2014)
In this paper we propose a framework for the support of mobile application with Quality of Service (QoS) requirements, such as voice or video, capable of supporting distributed, migration-capable, QoS-enabled applications on top of the Android Operating system.